The ketogenic diet and hypoxia promote mitophagy in the context of glaucoma - Morgan, Autumn B.; Fan, Yan; Inman, Denise M. (Frontiers in Cellular Neuroscience, 2024)
Mitochondrial homeostasis includes balancing organelle biogenesis with recycling (mitophagy). The ketogenic diet protects retinal ganglion cells (RGCs) from glaucomaassociated neurodegeneration, with a concomitant increase in mitochondrial biogenesis. This study aimed to determine if the ketogenic diet also promoted mitophagy. MitoQC mice that carry a pH-sensitive mCherry-GFP tag on the outer mitochondrial membrane were placed on a ketogenic diet or standard rodent chow for 5 weeks; ocular hypertension (OHT) was induced via magnetic microbead injection in a subset of control or ketogenic diet animals one week after the diet began. As a measure of mitophagy, mitolysosomes were quantified in sectioned retina immunolabeled with RBPMS for RGCs or vimentin for Müller glia. Mitolysosomes were significantly increased as a result of OHT and the ketogenic diet (KD) in RGCs. Interestingly, the ketogenic diet increased mitolysosome number significantly higher than OHT alone. In contrast, OHT and the ketogenic diet both increased mitolysosome number in Müller glia to a similar degree. To understand if hypoxia could be a stimulus for mitophagy, we quantified mitolysosomes after acute OHT, finding significantly greater mitolysosome number in cells positive for pimonidazole, an adduct formed in cells exposed to hypoxia. Retinal protein analysis for BNIP3 and NIX showed no differences across groups, suggesting that these receptors were equivocal for mitophagy in this model of OHT. Our data indicates that OHT and hypoxia stimulate mitophagy and that the ketogenic diet was additive for mitophagy in RGCs. The different response across RGCs and Müller glia to the ketogenic diet may reflect the different metabolic needs of these cell types.